Spatial Analysis of the Level of Accessibility of the Bobo Village Community in the Lore Lindu National park Area - Istiqamah, Nurul; Muis, Hasriani; Massiri, Sudirman Daeng; Baharuddin, Rhmadhani Fitrah; Misrah, Misrah; Toknok, Bau; Maiwa, Arman; Rahman, Abdul; Hulu, Amati Eltriman (Advance Sustainable Science, Engineering and Technology, 2024)
This research aims to determine the level of community accessibility in the Lore Lindu National Park Conservation area and determine the level of community accessibility in reaching areas that have been selected based on the provisions of the Cooperation Agreement (PKS) between Lore Lindu National Park and the Bobo Village Government in 2021. This research uses spatial analysis with five variables: land use, slope, and distance from roads, rivers and settlements. Determining the weight of each variable uses the Analytical Hierarchy Process (AHP) method with sources from the Bobo Village community and the Bobo Village Conservation Management Institute. The research results show that with the AHP method, land use has a significant effect on the level of community accessibility with a weight of 52.3%, followed by other parameters, namely slope of 26.8%, distance from the main road of 11.3%, distance from the river is 3, 4%, and distance from settlements is 6.2%. Furthermore, three classes of accessibility levels for the Bobo Village community were obtained: low level covering an area of 390.94 ha (96%), medium level covering an area of 17.76 ha (4%) and high level surrounding an area of 0.11 ha. (0%).